A composite solid-state electrolyte Na3Zr2Si2PO 12 / Na3PO4 and a preparation method and application thereof

CN118016988BActive Publication Date: 2026-10-27ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410303097.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2026-10-27
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

然而,NZSP/Na金属负极之间严峻的界面问题以及循环过程中无规则的枝晶生长问题是限制NZSP基全固态钠金属电池稳定循环的两大因素

Benefits of technology

[0022]1)本发明合成了一种新型复合固态电解质NZSP/Na3PO4,能够解决传统NZSP固态电解质的高界面电阻、差循环稳定性和低烧结密度等问题。相比于传统单相的NZSP固态电解质,这种新型复合固态电解质NZSP/Na3PO4改善了界面处的钠润湿性,降低了界面电阻以及提高了烧结密度,为钠离子固态电解质的设计改性工作提供了一种全新的思路和方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118016988B_ABST
    Figure CN118016988B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of sodium ion battery solid electrolytes, in particular to a composite solid electrolyte Na3Zr2Si2PO 12 / Na3PO4 and a preparation method and application thereof. Compared with a traditional single-phase NZSP solid electrolyte, the novel composite solid electrolyte NZSP / Na3PO4 improves sodium wettability at an interface, reduces interface resistance and improves sintering density, and provides a brand-new thought and method for design and modification of a sodium ion solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology for sodium-ion batteries, and specifically to a composite solid electrolyte Na3Zr2Si2PO4. 12 / Na3PO4, specifically designed a novel composite solid electrolyte Na3Zr2Si2PO4 12 Preparation method and electrochemical performance of / Na3PO4. Background Technology

[0002] With the increasing environmental problems caused by fossil fuels, a global energy transition is urgently needed, and the development of advanced energy storage systems is one of the important technological means to promote energy system reform. Over the past few decades, lithium-ion batteries with long cycle life have been successfully applied to portable electronic products and electric vehicles. However, due to the limited and high cost of lithium reserves, it is crucial to develop battery technologies that are more cost-effective and abundant in resources.

[0003] Sodium-ion batteries are widely considered a potential alternative to lithium-ion batteries due to their abundant raw material reserves, low cost, and electrochemical storage mechanism similar to that of lithium-ion batteries. However, current sodium-ion liquid electrolytes based on organic solvents such as carbonates and ethers typically suffer from several common drawbacks, including flammability, leakage, and a narrow electrochemical window. In contrast, solid-state electrolytes, with their high energy density and high safety, show greater potential for large-scale applications and are considered ideal materials for next-generation energy storage devices.

[0004] NASICON type Na3Zr2Si2PO 12 Sodium-ion solid electrolyte (NZSP) is a widely studied sodium-ion solid electrolyte. First discovered by Hong and Goodenough et al., NZSP possesses high ionic conductivity, a wide electrochemical window, outstanding mechanical properties, and good air stability, making it considered one of the most promising sodium-ion solid electrolytes. However, the severe interface problem between the NZSP / Na metal anode and the irregular dendrite growth during cycling are two major factors limiting the stable cycling of NZSP-based all-solid-state sodium metal batteries. Summary of the Invention

[0005] In view of this, the present invention synthesizes a novel composite solid electrolyte NZSP / Na3PO4 by solid-phase synthesis, which solves the above-mentioned problems of traditional NZSP solid electrolyte in one go.

[0006] It should be noted that traditional single-phase NZSP solid electrolytes suffer from problems such as high interfacial resistance, low sintering density, and poor cycling stability. To address these issues, this invention prepares a novel composite solid electrolyte, NZSP / Na3PO4. The second phase Na3PO4, generated in situ during the preparation process, regulates the chemical behavior of the NZSP / Na anode interface and inhibits dendrite growth during cycling.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A composite solid electrolyte Na3Zr2Si2PO 12 The method for preparing Na3PO4 specifically includes the following steps:

[0009] 1) Weigh out the raw materials SiO2, ZrO2, NH4H2PO4 and Na2CO3 according to the proportions, then add anhydrous ethanol, ball mill and dry;

[0010] 2) After drying in step 1), the powder is obtained by grinding, and then calcined to obtain block NZSP;

[0011] 3) After grinding the blocky NZSP until there is no particle feel, add anhydrous ethanol and ball mill. After drying and grinding, compress into tablets to obtain solid electrolyte tablets.

[0012] 4) Solid electrolyte masterbatch is spread between each layer of the solid electrolyte sheet, and then calcined to obtain the composite solid electrolyte Na3Zr2Si2PO4. 12 / Na3PO4.

[0013] Optionally, the molar ratio of the raw materials SiO2, ZrO2, NH4H2PO4 and Na2CO3 is 1:1:0.7:1.05 to 1:1:0.8:1.2;

[0014] Further, in step 1), the ball milling operation involves adding 40 10 mm zirconium dioxide grinding balls and 40 5 mm zirconium dioxide grinding balls, and then adding anhydrous ethanol as a liquid phase ball additive, and ball milling at 200-400 rad / min for 20-30 h.

[0015] Optionally, in step 2), the roasting operation is as follows: preheating is performed using a programmed temperature rise method, first maintaining a constant temperature of 600 ℃ for 4 h, and then raising the temperature to 1150 ℃ and maintaining a constant temperature for 4 h.

[0016] Optionally, in step 3), the ball milling operation involves adding 60 5 mm zirconium dioxide grinding balls and then adding anhydrous ethanol as a liquid-phase ball milling aid, and ball milling at 350-550 rad / min for 1-3 h.

[0017] Furthermore, the tableting operation is as follows: the obtained NZSP powder is tableted by first using a uniaxial press at a pressure of 5-7 tons for 40-80 seconds, followed by cold isostatic pressing at a pressure of 150-250 MPa for 6-8 minutes.

[0018] Optionally, in step 4), the roasting operation involves transferring the material to a muffle furnace for programmed heating, and maintaining the temperature at 1200 °C for 6 hours.

[0019] The second objective of this invention is to provide a composite solid electrolyte Na3Zr2Si2PO prepared by the method described above. 12 / Na3PO4.

[0020] The third objective of this invention is to provide a composite solid electrolyte Na3Zr2Si2PO prepared by the method described above. 12 Application of Na3PO4 in ion batteries.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] 1) This invention synthesizes a novel composite solid electrolyte, NZSP / Na3PO4, which solves the problems of high interfacial resistance, poor cycle stability, and low sintering density of traditional NZSP solid electrolytes. Compared with traditional single-phase NZSP solid electrolytes, this novel composite solid electrolyte, NZSP / Na3PO4, improves sodium wettability at the interface, reduces interfacial resistance, and increases sintering density, providing a completely new approach and method for the design and modification of sodium-ion solid electrolytes.

[0023] 2) This invention explores different ratios of sodium (Na2CO3) and phosphorus (NH4H2PO4) sources to generate different amounts of Na3PO4 secondary phase in situ during the synthesis of solid electrolytes. This allows for the screening of a novel composite solid electrolyte, NZSP-40NP, with optimal performance. Under this optimal ratio, the interfacial compatibility between the solid electrolyte and the sodium anode is improved, the sintering density is increased, and dendrite growth is suppressed during cycling. This invention provides a novel approach and method for synthesizing high-quality sodium-ion solid electrolytes, laying the foundation for the widespread application of the novel composite solid electrolyte NZSP / Na3PO4 in the future. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0025] Figure 1 X-ray diffraction patterns of composite solid electrolytes NZSP-20NP, NZSP-40NP, and NZSP-60NP obtained with sodium (Na2CO3) and phosphorus (NH4H2PO4) in excess of 20%, 40%, and 60%, respectively.

[0026] Figure 2 Scanning electron microscope images of composite solid electrolytes NZSP-20NP, NZSP-40NP, and NZSP-60NP.

[0027] Figure 3 The limiting current density curves of composite solid electrolytes NZSP-20NP, NZSP-40NP and NZSP-60NP at 60 °C are shown.

[0028] Figure 4 Wetting properties of composite solid electrolytes NZSP-20NP, NZSP-40NP and NZSP-60NP were tested.

[0029] Figure 5 Impedance spectra of sodium-symmetric cells for composite solid electrolytes NZSP-20NP, NZSP-40NP, and NZSP-60NP at room temperature.

[0030] Figure 6 The present invention prepares a composite solid electrolyte Na3Zr2Si2PO 12 Process flow diagram of Na3PO4. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0032] The term "embodiment" used herein, as an example, is not necessarily to be construed as superior to or better than other embodiments. Performance testing in the embodiments of this application, unless otherwise specified, employs conventional testing methods in the art. It should be understood that the terminology used in this application is merely for describing particular implementations and is not intended to limit the scope of this disclosure.

[0033] Unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; other experimental methods and technical means not specifically mentioned herein refer to experimental methods and technical means commonly used by one of ordinary skill in the art.

[0034] To better illustrate the content of this application, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this application can be implemented even without certain specific details. In the embodiments, some methods, means, instruments, and devices well known to those skilled in the art are not described in detail in order to highlight the main points of this application.

[0035] Without conflict, the technical features disclosed in the embodiments of this application can be combined arbitrarily, and the resulting technical solution belongs to the content disclosed in the embodiments of this application.

[0036] like Figure 6 This invention relates to the synthesis of a novel composite solid electrolyte NZSP / Na3PO4, comprising the following synthesis steps (to synthesize 20 g of Na 4.2 Zr2Si2P 1.4 O 12 Taking electrolyte as an example, abbreviated as NZSP-40NP):

[0037] Step 1: Prepare the necessary medicines for synthesis. See Table 1 for details.

[0038] Table 1

[0039] silicon dioxide <![CDATA[SiO2]]> 60.08 Aladdin Reagents (Shanghai) Co., Ltd. 99.5% trace metals basis 7631-86-9 Zirconium dioxide <![CDATA[ZrO2]]> 123.22 Aladdin Reagents (Shanghai) Co., Ltd. <![CDATA[99.99% metals basis (Hf or HfO2 removed)]]> 1314-23-4 Ammonium dihydrogen phosphate <![CDATA[NH4H2PO4]]> 115.03 Aladdin Reagents (Shanghai) Co., Ltd. 99.99% 7722-76-1 Sodium carbonate <![CDATA[Na2CO3]]> 105.99 Aladdin Reagents (Shanghai) Co., Ltd. 99.999% 497-19-8 Anhydrous ethanol <![CDATA[C2H6O]]> 46.07 Sinopharm AR 64-17-5

[0040] Step 2: Weigh out 4.3654 g of SiO2, 8.0859 g of Na2CO3, 8.9526 g of ZrO2 and 5.8501 g of NH4H2PO4 in sequence.

[0041] Step 3: Pour the weighed medicine into the ball mill jar, add 40 10 mm zirconium dioxide grinding balls and 40 5 mm zirconium dioxide grinding balls, and then add anhydrous ethanol as a liquid phase ball auxiliary agent.

[0042] Step 4: Place the grinding jar into a planetary ball mill and mill at 200-400 rad / min for 20-30 hours.

[0043] Step 5: After ball milling, place the open ball mill jar in a drying oven at 70-100 ℃ for thorough drying.

[0044] Step 6: Pour the fully dried medicine into a mortar and grind it thoroughly. Transfer it to a crucible and ensure that the powder in the crucible is sufficiently compacted before transferring it to a muffle furnace. Preheat the furnace using a programmed temperature rise method, first at 600 ℃ for 4 hours, then at 1150 ℃ for 4 hours.

[0045] Step 7: Grind the calcined NZSP blocks until there are no granules.

[0046] Step 8: Transfer the powder from the previous step to a ball mill jar, add 60 5 mm zirconium dioxide grinding balls, and then add anhydrous ethanol as a liquid-phase ball milling aid.

[0047] Step 9: Place the grinding jar into a planetary ball mill and mill at 350-550 rad / min for 1-3 hours.

[0048] Step 10: After ball milling, place the open ball mill jar in a drying oven at 70-100 ℃ for thorough drying.

[0049] Step 11: Pour the fully dried medicine into a mortar and grind it into powder.

[0050] Step 12: Compress the NZSP powder obtained in the previous step into tablets. First, use a single-axis press to press the tablets at a pressure of 5-7 tons for about 1 minute.

[0051] Step 13: Transfer the sheet obtained in the previous step to the mold for cold isostatic pressing at a pressure of 150-250 MPa, and let it stand for 6-8 minutes.

[0052] Step 14: Transfer the pressed sheets from the previous step to a crucible, spread an appropriate amount of solid electrolyte master powder between each layer of solid electrolyte sheets, and then transfer it to a muffle furnace for programmed heating. Heat to 1200 ℃ and hold at that temperature for 6 h. After sintering is complete, the novel composite solid electrolyte NZSP / Na3PO4 can be obtained.

[0053] To better understand the present invention, the following embodiments are provided for further detailed description of the present invention, but they should not be construed as limiting the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above-described invention are also considered to fall within the protection scope of the present invention.

[0054] Example 1

[0055] This invention relates to the synthesis of a novel composite solid electrolyte NZSP / Na3PO4, comprising the following synthesis steps (to synthesize 20g of Na 4.2 Zr2Si2P1.4 O 12 Taking electrolyte as an example, abbreviated as NZSP-40NP):

[0056] Step 1: Prepare the necessary medicines for synthesis. See Table 1 above for details.

[0057] Step 2: Weigh out 4.3654 g of SiO2, 8.0859 g of Na2CO3, 8.9526 g of ZrO2 and 5.8501 g of NH4H2PO4 in sequence.

[0058] Step 3: Pour the ground medicine into a ball mill jar, add 40 10 mm zirconium dioxide grinding balls and 40 5 mm zirconium dioxide grinding balls, and then add anhydrous ethanol as a liquid-phase ball milling aid.

[0059] Step 4: Place the grinding jar into a planetary ball mill and mill at 300 rad / min for 24 h.

[0060] Step 5: After ball milling, place the open ball mill jar in an 80 ℃ drying oven to dry thoroughly.

[0061] Step 6: After the medicine has been thoroughly dried, it is poured into a mortar and ground thoroughly. Then it is transferred to a crucible. After ensuring that the powder in the crucible is sufficiently compacted, it is transferred to a muffle furnace and the temperature is varied at 5 °C / min. First, the temperature is raised to 600 °C and held for 4 hours, then raised to 1150 °C and held for 4 hours, and finally cooled to room temperature.

[0062] Step 7: Grind the calcined NZSP blocks until there are no granules.

[0063] Step 8: Pour the powder from the previous step into a ball mill jar, add 60 5 mm zirconium dioxide grinding balls, and then add anhydrous ethanol as a liquid-phase ball milling aid.

[0064] Step 9: Place the grinding jar into a planetary ball mill and mill at 450 rad / min for 2 hours.

[0065] Step 10: After ball milling, place the open ball mill jar in an 80 ℃ drying oven to dry thoroughly.

[0066] Step 11: Pour the fully dried medicine into a mortar and grind it thoroughly into powder.

[0067] Step 12: Compress the NZSP powder obtained in the previous step into tablets. First, use a single-axis press to stand at a pressure of 7 tons for 1 minute.

[0068] Step 13: Transfer the sheet obtained in the previous step to the mold for cold isostatic pressing at a pressure of 200 MPa, and let it stand for 7 minutes.

[0069] Step 14: Transfer the cold isostatically pressed sheets from the previous step to a crucible, placing an appropriate amount of solid electrolyte masterbatch between each layer of solid electrolyte sheets. Then, transfer the crucible to a muffle furnace for programmed heating, varying the temperature at 5 °C / min. First, heat to 1200 °C and hold for 6 hours, then cool to room temperature. After sintering, a high-quality novel composite solid electrolyte NZSP / Na3PO4 is obtained.

[0070] Example 2

[0071] The implementation steps are the same as in Example 1, except that in the second step, the amount of Na2CO3 is changed to 6.9308 g and the amount of NH4H2PO4 is changed to 5.0144 g, that is, the sodium source and phosphorus source are in excess by 20%, and other conditions remain unchanged, and finally NZSP-20NP is obtained.

[0072] Example 3

[0073] The implementation steps are the same as in Example 1, except that in the second step, the amount of Na2CO3 is changed to 9.2411 g and the amount of NH4H2PO4 is changed to 6.6859 g, that is, the sodium source and phosphorus source are in excess by 60%, and other conditions remain unchanged, and finally NZSP-60NP is obtained.

[0074] To further demonstrate the beneficial effects of the present invention and to better understand it, the following experimental examples further illustrate the technical features disclosed in the present invention, but should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above-described invention, without inventive effort, are also considered to fall within the protection scope of the present invention.

[0075] like Figure 1 As shown in the figure, the solid electrolyte NZSP-20NP is a single-phase NZSP. As the amount of sodium source (Na2CO3) and phosphorus source (NH4H2PO4) increases, the Na3PO4 peak becomes stronger, indicating the presence of a second phase Na3PO4 in NZSP-40NP and NZSP-60NP.

[0076] like Figure 2 As shown in the figure, the density of the composite solid electrolyte NZSP / Na3PO4 increases with the increase of sodium source (Na2CO3) and phosphorus source (NH4H2PO4), indicating that the second phase Na3PO4 helps to improve the sintering density of the solid electrolyte.

[0077] like Figure 3 As shown in the figure, the composite solid electrolyte NZSP / Na3PO4 improves dendrite growth suppression compared to the single-phase NZSP electrolyte (NZSP-20NP), with NZSP-40NP exhibiting the best performance.

[0078] like Figure 4 As shown in the figure, the composite solid electrolyte NZSP-40NP exhibits the best wettability.

[0079] like Figure 5 As shown in the figure, the interface resistance of the composite solid electrolytes NZSP-40NP and NZSP-60NP is reduced to different degrees compared with the single-phase solid electrolyte NZSP-20NP. Among them, the interface resistance of NZSP-40NP is reduced to the minimum, indicating that the second phase Na3PO4 is beneficial to improve the negative electrode interface contact and thus reduce the interface resistance.

[0080] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite solid electrolyte Na3Zr2Si2PO 12 The method for preparing / Na3PO4 is characterized by, The method specifically includes the following steps: 1) Weigh out the raw materials SiO2, ZrO2, NH4H2PO4 and Na2CO3 according to the proportions, then add anhydrous ethanol, ball mill and dry; the molar ratio of the raw materials SiO2, ZrO2, NH4H2PO4 and Na2CO3 is 1:1:0.7:1.05~1:1:0.8:1.2; 2) After drying in step 1), the powder is obtained by grinding, and then calcined to obtain block NZSP; 3) After grinding the blocky NZSP until there is no particle feel, add anhydrous ethanol and ball mill. After drying and grinding, compress into tablets to obtain solid electrolyte tablets. 4) Solid electrolyte masterbatch is spread between each layer of the solid electrolyte sheet, and then calcined to obtain the composite solid electrolyte Na3Zr2Si2PO4. 12 / Na3PO4; In step 2), the roasting operation is as follows: preheating is performed using a programmed temperature rise method, first at 600 ℃ for 4 h, and then at 1150 ℃ for 4 h. In step 4), the roasting operation involves transferring the furnace to a muffle furnace for programmed heating, and maintaining the temperature at 1200 °C for 6 hours.

2. The composite solid electrolyte Na3Zr2Si2PO according to claim 1 12 The method for preparing / Na3PO4 is characterized by, In step 1), the ball milling operation involves adding 40 10 mm zirconium dioxide grinding balls and 40 5 mm zirconium dioxide grinding balls, and then adding anhydrous ethanol as a liquid phase ball milling agent, and ball milling at 200-400 rad / min for 20-30 h.

3. The composite solid electrolyte Na3Zr2Si2PO according to claim 1 12 The method for preparing / Na3PO4 is characterized by, In step 3), the ball milling operation is as follows: add 60 5 mm zirconium dioxide grinding balls, and then add anhydrous ethanol as a liquid-phase ball milling aid, and ball mill at 350-550 rad / min for 1-3 h.

4. The composite solid electrolyte Na3Zr2Si2PO according to claim 1 or 3 12 The method for preparing / Na3PO4 is characterized by, The tableting process is as follows: The obtained NZSP powder is tableted by first using a uniaxial press at a pressure of 5-7 tons and letting it stand for 40-80 seconds, followed by cold isostatic pressing at a pressure of 150-250 MPa and letting it stand for 6-8 minutes.

5. A composite solid electrolyte Na3Zr2Si2PO4 prepared by the method described in claim 1 12 / Na3PO4.

6. A composite solid electrolyte Na3Zr2Si2PO4 prepared by the method described in claim 1 12 / Na3PO4 or the composite solid electrolyte Na3Zr2Si2PO4 as described in claim 5 12 Application of Na3PO4 in sodium-ion batteries.